Supervision of Doctoral Students with Disabilities in South Africa: Issues, Trends and Reflections for Best Practice - (:unkn) unknown (My University, 2024)
The supervision of doctoral research is enmeshed in confounding experiences across multidisciplinary domains of knowledge and contexts. The situation seems more complicated if it involves doctoral students with disabilities in African educational landscapes. In relation to this, the paper discusses issues and trends that are prevalent in the supervision of doctoral students with disabilities in some South African institutions of higher learning. Further deliberations on evolving issues in the supervision of this group of students in a transforming educational system are made, respectively. The author also interrogates the influence of attitudinal factors in the supervision process, challenges experienced by supervisors and lastly makes suggestions for reflective practice.
Keywords: African Research